343. A public facing survey on radiation risk perception set up within the CONCERT European Joint Programme: preliminary results. (December 2018) - Grande, Sveva; Monaca, Sara Della; Dini, Valentina; Palma, Alessandra; Fattibene, Paola; Rosi, Antonella; Tabocchini, Maria Antonella; Duranova, Tatiana; Perko, Tanja; Pölzl-Viol, Christiane; Tomkiv, Yevgeniya; Turcanu, Catrinel; et al.
Abstract : Purpose: Work package 5 of the CONCERT European Joint Programme deals with stakeholder engagement and communication strategies in radiation protection. In particular, Task 5.3 of the WP5 concerns the development of survey activities for a more efficient interaction with civil society and the use of social media for public communication. This task falls within the scope of the CONCERT consortium answering the needs in radiation protection for the public, occupationally exposed people, and patients in medicine. Methods: A public facing e-survey has been developed and launched in June 2017 on the CONCERT website. To reach a larger segment of the population, trying to minimize the impact of linguistic barriers, the text of the survey was translated in fourteen European languages: English, Bulgarian, Croatian, Dutch, Estonian, French, German, Greek, Latvian, Italian, Polish, Portuguese, Slovak and Spanish. The deadline was 31st December 2017. Results: The survey aims to gauge the perception of radiation risk amongst a wide range of people who are not radiation specialists and their opinion on information that would be helpful to a general audience to understand radiation risk. The first part of the survey includes a section about the responders' personal information, their attitude towards science and technology, their satisfaction towards the actors in the radiation protection domain and the actions undertaken by RP authorities, their opinion towards the communication channels about radiological risk. Fig. 1 shows the question about benefits and detriments. In the second part of the survey, specific sections are addressed to particular categories of people such as professionally exposed persons, medically exposed patients or people with a cultural interest for radiation protection issues (such as journalists or students). Conclusions: The strategies adopted to raise awareness and encourage responses in Italy will be presented together with the preliminary analysis of the results.